On the Trail of Preventing Meningococcal Disease: A Survey of Students Planning to Travel to the United States. Issue 4 (27th May 2013) - Huang, Hsien‐Liang; Cheng, Shao‐Yi; Lee, Long‐Teng; Yao, Chien‐An; Chu, Chia‐Wei; Lu, Chia‐Wen; Chiu, Tai‐Yuan; Huang, Kuo‐Chin
Abstract: Background: College freshmen living in dormitories are at increased risk for meningococcal disease. Many students become a high‐risk population when they travel to the United States. This study surveyed the knowledge, attitudes toward, and behavior surrounding the disease among Taiwanese college students planning to study in the United States, and to identify factors that may affect willingness to accept meningococcal vaccination. Methods: A cross‐sectional survey of college students going to study in the United States was conducted in a medical center‐based travel medicine clinic. Background information, attitudes, general knowledge, preventive or postexposure management, and individual preventive practices were collected through a structured questionnaire. Results: A total of 358 students were included in the final analysis. More than 90% of participants believed that preventing meningococcal disease was important. However, fewer than 50% of students accurately answered six of nine questions exploring knowledge of the disease, and only 17.3% of students knew the correct management strategy after close contact with patients. Logistic regression analysis showed that students who understood the mode of transmission (odds ratio: 3.21, 95% CI = 1.117–9.229), medication management (1.88, 1.045–3.38), and epidemiology (2.735, 1.478–5.061) tended to be vaccinated. Conclusions: Despite an overall positive attitude toward meningococcal vaccination, there was poor knowledge about meningococcal disease. Promoting education on the mode of transmission, epidemiology, and pharmacological management of the disease could increase vaccination rates. Both the governments and travel medicine specialists should work together on developing an education program for this high‐risk group other than just requiring vaccination.